A risk- and cost-related approach for the global seismic safety assessment of existing buildings - Xavier Romão (2012)
A probabilistic methodology is proposed to assess the seismic safety of a building using global performance metrics and to determine if it conforms to a given limit state. The performance metrics are the probability of occurrence of the limit state, the corresponding expected loss associated to the repair of the building, and the corresponding number and type of mechanisms that occur. By considering these parameters, the scope of the limit state definitions of current codes is extended to establish adequate risk- and cost-related limit state definitions. The performance of two reinforced concrete structures is then analysed by the proposed method.